Enhancing proline-rich antimicrobial peptide action by homodimerization: influence of bifunctional linker. Issue 8 (1st February 2022) - Li, Wenyi; Lin, Feng; Hung, Andrew; Barlow, Anders; Sani, Marc-Antoine; Paolini, Rita; Singleton, William; Holden, James; Hossain, Mohammed Akhter; Separovic, Frances; O'Brien-Simpson, Neil M.; Wade, John D.
Abstract : Homodimerization of a proline-rich antimicrobial peptide via bioconjugation to perfluoroaromatic linkers confers increased antimicrobial, antibiofilm and immunomodulatory activity. The dimers are promising new therapeutic leads against WHO priority multidrug resistant bacteria. Abstract : Antimicrobial peptides (AMPs) are host defense peptides, and unlike conventional antibiotics, they possess potent broad spectrum activities and, induce little or no antimicrobial resistance. They are attractive lead molecules for rational development to improve their therapeutic index. Our current studies examined dimerization of the de novo designed proline-rich AMP (PrAMP), Chex1-Arg20 hydrazide, via C-terminal thiol addition to a series of bifunctional benzene or phenyl tethers to determine the effect of orientation of the peptides and linker length on antimicrobial activity. Antibacterial assays confirmed that dimerization per se significantly enhances Chex1-Arg20 hydrazide action. Greatest advantage was conferred using perfluoroaromatic linkers (tetrafluorobenzene and octofluorobiphenyl) with the resulting dimeric peptides 6 and 7 exhibiting potent action against Gram-negative bacteria, especially the World Health Organization's critical priority-listed multidrug-resistant (MDR)/extensively drug-resistant (XDR) Acinetobacter baumannii as well as preformed biofilms. Mode of action studies indicated these lead PrAMPs can interact with both outer and inner bacterial membranes to affect the membrane potential and stress response. Additionally, 6 and 7 possess potent immunomodulatory activity and neutralise inflammation via nitric oxide production in macrophages. Molecular dynamics simulations of adsorption and permeation mechanisms of the PrAMP on a mixed lipid membrane bilayer showed that a rigid, planar tethered dimer orientation, together with the presence of fluorine atoms that provide increased bacterial membrane interaction, is critical for enhanced dimer activity. These findings highlight the advantages of use of such bifunctional tethers to produce first-in-class, potent PrAMP dimers against MDR/XDR bacterial infections.